Dexmedetomidine Preconditioning Protects Rats from Renal Ischemia–Reperfusion Injury Accompanied with Biphasic Changes of Nuclear Factor-Kappa B Signaling. (17th April 2020) - Bao, Naren; Tang, Bing; Wang, Junke
Abstract : Acute kidney injury (AKI) is one of the most common and troublesome perioperative complications. Dexmedetomidine (DEX) is a potent α 2-adrenoceptor ( α 2-AR) agonist with anti-inflammatory and renoprotective effects. In this study, a rat renal ischemia–reperfusion injury (IRI) model was induced. At 24 h after reperfusion, the IRI-induced damage and the renoprotection of DEX preconditioning were confirmed both biochemically and histologically. Changes in nuclear factor-kappa B (NF- κ B), as well as its downstream anti-inflammatory factor A20 and proinflammatory factor tumor necrosis factor- α (TNF- α ), were detected. Atipamezole, a nonselective antagonist, was then added 5 min before the administration of DEX to further analyze DEX's effects on NF- κ B, and another anti-inflammatory medicine, methylprednisolone, was used in comparison with DEX, to further analyze DEX's effects on NF- κ B. Different concentrations of DEX (0 nM, 0.1 nM, 1 nM, 10 nM, 100 nM, 1 μ M, and 10 μ M) were applied to preincubated human renal tubular epithelial cell line (HK-2) cells in vitro. After anoxia and reoxygenation, the MTT (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide) tetrazolium assay and enzyme-linked immunosorbent assay (ELISA) were performed to evaluate the levels of NF- κ B downstream anti-inflammatory cytokines. The results showed that, unlike methylprednisolone, DEX preconditioning led to a time-dependent biphasic change (first activation then inhibition) of NF- κ B in the rat renal IRI models that were given 25 μ g/kg i.p. It was accompanied by a similarly biphasic change of TNF- α and an early and persistent upregulation of A20. In vitro, DEX's cellular protection showed a concentration-dependent biphasic change which was protective within the range of 0 to 100 nM but became opposite when concentrations are greater than 1 μ M. The changes in the A20 and NF- κ B messenger RNA (mRNA) levels were consistent with the renoprotective ability of DEX. In other words, DEX preconditioning protected the rats from renal IRI via regulation biphasic change of NF- κ B signaling.